Validación de la escala de agresión entre pares para adolescentes, factor de ciberbullying y subescala de victimización en estudiantes arequipeños - Rivera Calcina, Carlos Renzo (2019)
Bullying has become a prevalent phenomenon in Latin American countries. Unfortunately, the lack of accurate and valid instruments to measure it has made it very difficult to produce proper research. The goal of the present study was to validate the Peer-Aggression Scale (Cajigas, Khan, Luzardo, Najson, & Zalmavide, 2004) adding a factor that measures cyberbullying and a scale for victimization. Sampling was done through a probabilistic multi-stage stratified proportional allocation process. It consisted finally of 3978 students from all secondary grades of 19 public, private, and charter schools from the Metropolitan Area of Arequipa ( = 14.41 years old). We found satisfactory results for its construct validity based on exploratory and confirmatory analysis. We extracted 11 factors (8 for the original scale and 3 to incorporate factor of cyberbullying and victimization subscale). In addition, the indexes of reliability were suitable in most of the sub-scales, although the values were quite low for the sub-scales of attitudes toward aggression and external influences. Our results are consistent with psychometric properties found in studies conducted in Uruguay, and Chile.